Iceland's best kept secret. (March 2014) - Berg, Sylvia E.; Troll, Valentin R.; Burchardt, Steffi; Riishuus, Morten S.; Krumbholz, Michael; Gústafsson, Ludvik E.
<x xml:space="preserve">Abstract</x> The 'forgotten fjords' and 'deserted inlets' of NE‐Iceland, in the region between Borgarfjörður Eystri and Loðmundarfjörður, are not only prominent because of their pristine landscape, their alleged elfin settlements, and the puffins that breed in the harbour, but also for their magnificent geology. From a geological point of view, the area may hold Iceland's best kept geological secret. The greater Borgarfjörður Eystri area hosts mountain chains that consist of voluminous and colourful silicic rocks that are concentrated within a surprisingly small area (Fig. 1), and that represent the second‐most voluminous occurrence of silicic rocks in the whole of Iceland. In particular, the presence of unusually large volumes of ignimbrite sheets documents extremely violent eruptions during the Neogene, which is atypical for this geotectonic setting. As a group of geoscientists from Uppsala University (Sweden) and the Nordic Volcanological Center (NordVulk, Iceland) we set out to explore this remote place, with the aim of collecting material that may allow us to unravel the petrogenesis of these large volumes of silicic rocks. This effort could provide an answer to a long‐standing petrological dilemma; the question of how silicic continental crust is initially created. Here we document on our geological journey, our field strategy, and describe our field work in the remote valleys of NE‐Iceland.